2015
DOI: 10.1111/epi.13026
|View full text |Cite
|
Sign up to set email alerts
|

Perineuronal net degradation in epilepsy

Abstract: SUMMARYObjective: We previously reported loss of perineuronal net (PN) immunohistochemical staining around parvalbumin-positive interneurons in the hippocampus of rats after an episode of status epilepticus (SE). We hypothesized that the loss of the PN could alter seizure susceptibility and that matrix metalloproteinases (MMPs) were candidates for degradation of the PN following SE. Methods: The pilocarpine chemoconvulsant rodent epilepsy model was used to characterize the degradation of the aggrecan component… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
80
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 82 publications
(84 citation statements)
references
References 40 publications
(47 reference statements)
4
80
0
Order By: Relevance
“…AS mice with the capacity for conditional reinstatement of maternal Ube3a gyrus is a reliable anatomical correlate of enhanced epileptogenesis in flurothyl-kindled AS mice. Converging lines of evidence show that seizures can alter components of PNNs, but the specific proteins involved, and the direction and duration of changes may vary depending on a number of factors -the age of the animal, the seizure induction method, the brain region studied, and the time elapsed following seizure (27)(28)(29)(30). Each of these factors, and hence the nature of the relationship between abnormal PNN deposition and epileptogenesis in AS model mice, remains to be rigorously investigated.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…AS mice with the capacity for conditional reinstatement of maternal Ube3a gyrus is a reliable anatomical correlate of enhanced epileptogenesis in flurothyl-kindled AS mice. Converging lines of evidence show that seizures can alter components of PNNs, but the specific proteins involved, and the direction and duration of changes may vary depending on a number of factors -the age of the animal, the seizure induction method, the brain region studied, and the time elapsed following seizure (27)(28)(29)(30). Each of these factors, and hence the nature of the relationship between abnormal PNN deposition and epileptogenesis in AS model mice, remains to be rigorously investigated.…”
Section: Resultsmentioning
confidence: 99%
“…We next questioned whether gross changes in the hippocampal extracellular matrix, perineuronal nets (PNNs) in particular, might associate with the exaggerated epileptogenesis phenotype in flurothyl-kindled AS model mice. PNNs are uniquely localized around specific neurons to regulate synapse stability and plasticity in the adult CNS (26), and have been associated with epileptic activity during early and late development (27)(28)(29)(30). To examine a possible link between changes in PNNs and enhanced epileptogenesis in AS model mice, we labeled PNNs with biotinylated Wisteria floribunda agglutinin (WFA) in flurothyl-kindled mice before (Supplemental Figure 3), or 1 hour after (Figure 4, A and B), retest.…”
Section: Resultsmentioning
confidence: 99%
“…It is mainly responsible for the storage, conversion, and orientation of long-term memory, and it has important roles in information processing. Repeated convulsions in rodents have far-reaching and harmful effects on hippocampal long-term memory, which can reduce the plasticity of hippocampal information processing [38]. Hippocampus is the best area to observe the pharmacodynamic changes in cognitive and emotional disorders caused by epileptic injury [39,40].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have demonstrated that seizures result in changes in the components of ECM, including increases in the expression of tenascin‐C (Mercado‐Gomez et al, ) and neurocan (Okamoto et al, ) and decreases in aggrecan and HAPLN type 1 (McRae et al, ; for reviews see Dityatev and Fellin, ; McRae and Porter, ). Compromised structural integrity of PNNs has been found in the rodent brain with pilocarpine‐induced status epilepticus (McRae et al, ; Rankin‐Gee et al, ). It is noteworthy that enzymatic degradation of ECM by chondroitinase ABC lowered the threshold for myoclonic seizures after pentylenetetrazole treatment but delayed the onset and duration of Racine stage 4/5 seizure (Rankin‐Gee et al, ).…”
Section: Implications Of Pnns Around Fast‐spiking Inhibitory Interneumentioning
confidence: 99%
“…Compromised structural integrity of PNNs has been found in the rodent brain with pilocarpine‐induced status epilepticus (McRae et al, ; Rankin‐Gee et al, ). It is noteworthy that enzymatic degradation of ECM by chondroitinase ABC lowered the threshold for myoclonic seizures after pentylenetetrazole treatment but delayed the onset and duration of Racine stage 4/5 seizure (Rankin‐Gee et al, ). Furthermore, a mouse line with a constitutive knockout of tenascin‐R, one of the major components of PNNs, displayed reduced perisomatic inhibition, increased excitatory transmission, and impaired long‐term potentiation (Saghatelyan et al, ).…”
Section: Implications Of Pnns Around Fast‐spiking Inhibitory Interneumentioning
confidence: 99%